TYPHOID MARY - Yuldasheva Khusnora Khusinboy kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article explores the historical and medical significance of Mary Mallon—widely  known  as  “Typhoid  Mary”—as  the  first  identified  asymptomatic carrier of typhoid fever in the United States. It examines the implications of her case for modern public health policy, epidemiological surveillance, and the ethical tensions between  individual  liberties  and  collective  safety.  Drawing  on  primary  historical records and contemporary analysis, the article reflects on how Typhoid Mary’s story influenced  early  20th-century  approaches  to  quarantine,  disease  control,  and  the evolving perception of carriers in infectious disease transmission.